Power Quality Improvement in Fourteen Bus System using Non-Conventional Source Based ANN Controlled DPFC System - Akhib Khan Bahamani; G.M. Sreerama Reddy; V. Ganesh (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
DPFC can be used to improve receiving end voltage of fourteen bus system. This paper shows the conception and simulation of wind and solar based distribution power flow controller for sag compensation and ohmic loss reduction. The objectives of this work are to improve the voltage and reduce the line losses. Fourteen bus systems with DPFC in open loop is simulated. Fourteen bus system with DPFC in closed loop using PI and ANN are also simulated and the results are presented. The comparative study is presented to demonstrate the improvement in dynamic response of ANN controlled DPFC system. ANN is observed to provide better control than has other controllers and improved damping characterises.